Analisis Kebijakan Zonasi Pada Penerimaan Peserta Didik Baru Terhadap Titip Kartu Keluarga Di Kelurahan Kebonsari Kota Surabaya - Robbiatul Adawiyah Awahah; Achluddin Ibnu Rochim (Jurnal Media Administrasi, 2023)
The application of the zoning system to the acceptance of new students gives rise to various perceptions in society. Likewise, what happened in the Kebonsari Village community was that the implementation of the zoning system caused them to have negative and positive perceptions. The purpose of this research is to see the condition of Kebonsari Village regarding zoned school registration with the widespread transfer of Family Cards. This type of research is descriptive with a qualitative approach. By using observation, interview and documentation data collection techniques. The research was conducted in Kebonsari Village. The conclusion from the research results shows that in Kebonsari Village where the Family Card was moved due to minimal schooling, only in Kebonsari Village, there are several residents who are not or are not in that domicile. They only include a Family Card with a Surabaya address but they are outside the city of Surabaya for various reasons. This case was discovered by the author while carrying out the Kalimasada program by surveying the residences of residents in the sub-district. This could cause them to be suspected of not knowing their residency and being blocked from being registered in the Sistem Informasi Administrasi Kependudukan (SIAK) because the data is blocked because these residents do not actually live in that area.